2003
DOI: 10.1373/49.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Throughput DNA Microarrays to Identify Biomarkers for Bladder Cancer

Abstract: Background: Numerous markers have been described to correlate to some extent with tumor stage and prognosis of patients with bladder cancer. The power of many of these biomarkers in detecting superficial disease or predicting the clinical outcome of individual tumors is limited, and alternative markers are still in demand. High-throughput microarrays represent novel means for cancer research and tumor marker discovery. Approach: The aim of this report was to discuss the application of DNA technologies to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
(48 reference statements)
1
37
0
1
Order By: Relevance
“…Hierarchical clustering separated tumors into two clearly distinct groups, superficial and muscle invasive, similar to previous reports (12,13,16,17). When a set of nine bladder tumor cell lines was included in the unsupervised clustering, eight of nine (all derived from advanced tumors) were grouped in a separate subcluster with five muscle-invasive tumors.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Hierarchical clustering separated tumors into two clearly distinct groups, superficial and muscle invasive, similar to previous reports (12,13,16,17). When a set of nine bladder tumor cell lines was included in the unsupervised clustering, eight of nine (all derived from advanced tumors) were grouped in a separate subcluster with five muscle-invasive tumors.…”
Section: Discussionsupporting
confidence: 77%
“…In bladder cancer, expression patterns have identified gene signatures that are associated with tumor stage (16,17) and superficial recurrence (16). However, the number of muscle-invasive tumors reported in those studies was small, and robust outcome classification models for the invasive tumors were not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUC1 levels are high in advanced disease and serum MUC1 levels may be useful in monitoring disease, (11). It is suggested that high-throughput DNA micro-arrays will soon move from being technology restricted to research and clinical laboratories (12). Methylation of the p16 (INK4a) promoter may be a new type of tumor marker in bladder cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the mutated DNA can provide diagnostically useful molecular markers (2 ). Among them are point mutations, which involve a change in a single base pair in the DNA, such as those occurring in the p53 and K-ras genes (3)(4)(5). The detection of such point mutations is useful in screening for cancers (6 ) as well as for typing of cancers to optimize treatment protocols (7 ).…”
mentioning
confidence: 99%